(untitled) (INNOVATIVE ECONOMY, 2025)
Kvasnytsia O.V., Darmohrai I.V., Novitskyi M.R. BANK INVESTMENTS IN PRIORITY PROJECTS OF GREEN TRANSFORMATION: UKRAINE’S EUROPEAN INTEGRATION CHOICE Purpose. The aim of the article is to substantiate the role of bank investments as a key instrument for financing the green transformation and European integration priorities of Ukraine, taking into account the European Union’s strategic approaches to infrastructure development, energy security, digitalization, and sustainable economic growth; and to develop an adaptive three-level financing model that combines national initiatives, EU instruments, and public-private partnership mechanisms to ensure sustainable development and integration of Ukraine into a single European space. Methodology of research. The study employs a systemic approach to analyzing the European Union’s financial strategies in the context of their adaptation to national conditions. The comparative analysis method is used to contrast European financing instruments for infrastructure, energy, and digital projects with domestic initiatives. The structural-logical method enables the identification of interconnections between banking investments, public-private partnerships, and European integration processes. Elements of institutional analysis are applied to assess the role of European financial institutions in supporting the resilience and development of Ukraine’s economy. Findings. The article examines the role of bank investments in ensuring green transformation and supporting Ukraine’s European integration course in line with the EU’s strategic priorities in the areas of defense, energy, competitiveness, and support for Ukraine. It highlights that these priorities create conditions for infrastructure modernization, acceleration of reforms, and Ukraine’s rapprochement with EU membership. Based on an analysis of the EU Modernization Fund’s experience, the article substantiates the feasibility of adapting similar mechanisms to upgrade Ukraine’s energy infrastructure and integrate it with European markets. It is noted that the EU’s practical security strategies include investments in the training and equipping of the Armed Forces of Ukraine, as well as preparations for the opening of the “Fundamentals” cluster within the framework of the enlargement policy. It is determined that investments by the banking sector in transport infrastructure – within the framework of the Connecting Europe Facility programs, the greening of ports, the digitization of traffic management, and solidarity projects – contribute to the achievement of sustainable development goals and the harmonization of Ukraine’s transport system with EU standards. Originality. The paper further develops a three-level model of strategic financing that combines existing financial instruments, national programs, and EU cohesion policy. It is argued that the absence of such a model could threaten debt sustainability and slow down European integration processes. Priority areas for modernisation have been identified: development of railway infrastructure (TEN-T, ERTMS), greening of ports, and formation of urban mobility hubs within the EU’s decarbonisation policy. It is proven that the implementation of European standards of risk management and transparency can increase the role of the Ukrainian banking sector in mobilizing private capital, developing public-private partnerships, and attracting foreign investment. Practical value. The obtained results regarding Ukraine’s European integration priorities in the field of green transformation reveal opportunities for infrastructure modernization, enhanced security, and economic growth through the mobilization of banking investments. The implementation of such approaches will contribute to strengthening the financial stability of the state and ensuring long-term economic growth based on sustainable development. Key words: sustainable development, digitalization, credit resources, territorial communities, investment, public finance, green investments, financial resources, risk, security.